The Association Between Residential Proximity to A Major Roadway and the Prevalence of Environmentally Influenced Conditions - Indorato, Daniel C. (Archives of Clinical and Biomedical Research, 2018)
Background: Motor vehicles are the prime culprit of air-pollution, and could be possibly linked to the development of widely evident health hazards. Objective: The purpose of the current study was to examine the association between residential proximity to a major roadway and the prevalence of metabolic disorders, respiratory diseases, and stress levels. Materials and Methods: A cross-sectional survey was administered to 99 randomly selected subjects (Males: 33, Females 66) aged between 18 and 74 years, who lived at a residence for a minimum one to five years. Results: The findings in the current study reveal an increase in the prevalence of anxiety, depression, asthma, allergies, attention deficit disorder, type 2 diabetes, hypertension, and self-reported stress seen in individuals who live within five miles of a major highway. A negative correlation was observed between residential distance from a major highway and the prevalence of asthma/allergies and type 2 diabetes.